Spin-dependent quantum theory of high-order above-threshold ionization - Zille, D.; Seipt, D.; Moeller, M.; Fritzsche, S.; Paulus, Gerhard G.; Milosevic, D. B. (Physical Review A, 2017)
The strong-field-approximation theory of high-order above-threshold ionization of atoms is generalized to include the electron spin. The obtained rescattering amplitude consists of a direct and exchange part. On the examples of excited He atoms as well as Li+ and Be++ ions, it is shown that the interference of these two amplitudes leads to an observable difference between the photoelectron momentum distributions corresponding to different initial spin states: Pronounced minima appear for singlet states, which are absent for triplet states.
CRIS-Team Scopus Importer:2023-04-20